PENINGKATAN KESADARAN HUKUM MASYARAKAT TERHADAP PENTINGNYA LINGKUNGAN HIDUP YANG BAIK DAN SEHAT DI RT 01/RW 01 KELURAHAN ALAK KECAMATAN ALAK KOTA KUPANG - Asnawi, Norani; Nuban, Detji K E R; Bunga, Gerald A; Kian, Darius A (Universitas Mataram, 2024)
Although there are a number of regulations that regulate and guarantee human rights to a good and healthy environment, in reality there are still those who live in unhealthy environments such as those experienced by scavengers who live temporarily in tents set up along the Final Processing Site (TPA) and the community living in the RT 01/RW 01 area of ​​Alak Village, Alak District, Kupang City. In carrying out their activities, the community and scavengers wear simple equipment, such as hats, glasses and used shoes and head coverings to avoid heat and dust. Only a few still care about wearing masks and face coverings when carrying out scavenging and managing waste. The results obtained by the community and scavengers are certainly not comparable to the risks or negative impacts that can be caused to health. This activity is motivated by several problems, namely the lack of knowledge and understanding of partners or target communities regarding regulations in the field of environment and health, the lack of knowledge and understanding of partners regarding the negative impacts that can be caused. Therefore, this community service activity aims to provide knowledge and understanding to partners regarding regulations in the field of environment and health, provide knowledge and understanding to partners regarding the negative impacts that can be caused to health. The implementation method consists of observation and problem identification activities, counseling activities, and evaluation. Through counseling activities, partners gain knowledge and understanding of the importance of a good and healthy environment. Furthermore, based on the evaluation results, it is known that this community service activity is running well and satisfactorily, namely by increasing legal awareness for partners